2000
DOI: 10.2307/3284917
|View full text |Cite
|
Sign up to set email alerts
|

Tetracapsula renicola n. sp. (Myxozoa:Saccosporidae); The PKX Myxozoan: The Cause of Proliferative Kidney Disease of Salmonid Fishes

Abstract: Proliferative kidney disease (PKD) of salmonid fishes is caused by the extrasporogonic stage of an enigmatic myxozoan, referred to as PKX. Sporogenesis occurs in the renal tubules, resulting in monosporous pseudoplasmodia. The spores are ovoid with indistinguishable valves and measure 12 microm in length and 7 microm in width. Two spherical polar capsules (2 microm diameter) with 4 coils occur at the anterior end of the spore. Prominent capsulogenic cell nuclei posterior to the polar capsules are evident in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 8 publications
2
66
0
Order By: Relevance
“…Phylogenetic trees produced by 18S rDNA sequences of myxosporeans available in the GenBank largely agreed with Shulman's (1966) phylogenetic hypotheses, and have revealed the importance of several phenotypic features in species identification (Kent et al 2000(Kent et al , 2001. Based on the 18S rDNA sequences of 10 myxosporean species, Andree et al (1999) found that parasite species were related mostly by their location in the tissue of the fish host.…”
Section: Introductionsupporting
confidence: 49%
“…Phylogenetic trees produced by 18S rDNA sequences of myxosporeans available in the GenBank largely agreed with Shulman's (1966) phylogenetic hypotheses, and have revealed the importance of several phenotypic features in species identification (Kent et al 2000(Kent et al , 2001. Based on the 18S rDNA sequences of 10 myxosporean species, Andree et al (1999) found that parasite species were related mostly by their location in the tissue of the fish host.…”
Section: Introductionsupporting
confidence: 49%
“…Concerning the molecular based division of my xosporeans into the major freshwater and marine clades (Kent et al 2000, Fiala 2006, Bartošová et al 2009, Holzer et al 2010, we note that the clade comprising Zschokkella auratis sp. nov. constitutes yet another exception to this main division.…”
Section: Discussionmentioning
confidence: 99%
“…A 17th SSU rDNA sequence ter med Z. mugilis Sitjà-Bobadilla & Al va rez-Pellitero, 1993 remains in GenBank; however, this species was recently revised to Ellipsomyxa mugilis (Køie & Karlsbakk 2009), having also been linked to its correspondent actinosporean stage developing in an estuarine polychaete (Rangel et al 2009(Rangel et al , 2012. Overall, the molecular information regarding Myxo sporea has revealed the existence of 2 main clades dividing freshwater and marine species (Kent et al 2000, Fiala 2006, Bartošová et al 2009, Holzer et al 2010, for which myxosporean parasites infecting anadromous hosts, as well as some species of Henneguya, Chloromyxum, Ceratomyxa, Myxo bolus, Myxidium, Parvicapsula, and Sphaero myxa, constitute exceptions (Diamant et al 2004, Fiala 2006, Rocha et al 2013). Phylogenetic analyses have also shown that most myxosporeans cluster according to their host tissue tropism rather than by spore morphology or host species (Eszterbauer 2004, Holzer et al 2004, Fiala 2006, Bartošová et al 2009, Fiala & Bartošová 2010, and the genus Zschokkella is no ex ception (Holzer et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…AF201375, Kent et al 2000), and in combination with a general ssu PCR primer, Ecf, they were used to pick out the first part of the ssu from P. pseudobranchicola (Table 2). In addition, PCR primers and diagnostic primers for Parvicapsula spp.…”
Section: Methodsmentioning
confidence: 99%